2000
DOI: 10.1177/0148607100024006337
|View full text |Cite
|
Sign up to set email alerts
|

Intralipid‐Based Short‐Term Total Parenteral Nutrition Does Not Impair Small Intestinal Mucosa‐Related Cellular Immune Reactivity in the Healthy Rat

Abstract: In healthy rodents, short-term lipid-based and carbohydrate-based TPN regimens lead to limited mucosal atrophy with preserved surface architecture compared with enteral feeding. However, peripheral and mesenteric cellular immune responsiveness after both TPN regimens remained comparable to enterally fed reference animals. Therefore, mesenteric and systemic cellular immune reactivity does not appear to be impaired by lipid-based or carbohydrate-based TPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…6,7 Gogos et al 47 not impaired by the administration of LE in rats. 48 In contrast, Monson et al 49 found that administration of SOE leads to a rise in the total circulating T cell number in pre-and postoperative patients.…”
Section: Discussionmentioning
confidence: 94%
“…6,7 Gogos et al 47 not impaired by the administration of LE in rats. 48 In contrast, Monson et al 49 found that administration of SOE leads to a rise in the total circulating T cell number in pre-and postoperative patients.…”
Section: Discussionmentioning
confidence: 94%